O21 Should we opportunistically treat rectal Chlamydia trachomatis infection in men who have sex with men presenting with non-specific urethritis?. (23rd May 2012) - Rayment, M; Bull, L; Mandalia, S; Boag, F; Nwokolo, N; Jones, R
Abstract : Background: Infection of the rectum with Chlamydia trachomatis (CT) is highly prevalent among men who have sex with men (MSM) attending our service (c. 8%). Our guidelines advise different antibiotics for the treatment of non-specific urethritis (NSU) (azithromycin 1 g as a single dose) and for rectal CT infection (doxycycline 100 mg twice daily for 7 days). MSM receiving treatment for NSU require recall if they are latterly found to have concurrent rectal CT. Should we therefore use doxycycline first line in MSM presenting with NSU? Aims: To determine the proportion of MSM diagnosed with NSU with rectal CT infection; to identify independent predictors of having rectal CT. Methods: The clinic database identified sequential MSM diagnosed with NSU over 6 months. Co-variables collected: age, sexual history, HIV status, contact history and the presence of rectal symptoms. Only men accepting rectal sampling were included. Univariate and multivariable logistic regression analyses were undertaken. Results: 566 MSM presenting with NSU were identified, of whom 130 (23%) were diagnosed with CT infection of at least one anatomical site. Of this group, 99 were included in the analysis. The overall prevalence of rectal CT infection was 38% (38/99). In men reporting a history of unprotected receptive anal intercourse (UPRAI) in the preceding 6 months, the prevalence was 61% (31/51); in those without it was 7.1% (14/48). In MSM reporting rectal symptoms, the prevalence was 90% (9/10); in those without: 33% (29/89). In the multivariable model, the only independent predictors of risk of rectal CT infection were UPRAI and rectal symptoms (see Abstract O21 table 1 ). Discussion: First line treatment of NSU in MSM could be modified based on the likelihood of concurrent CT infection. In men reporting UPRAI in the preceding 6 months, or reporting rectal symptoms, it would be reasonable to offer treatment of NSU with doxycycline. In all other patients, we propose continuing to use azithromycin first line, with subsequent recall for further treatment as necessary.